The Impact of Oil Palm Plantations on The Achievement of Sustainability Development Goals From An Islamic Economic Perspective - Anton Priyo Nugroho; Suci Dayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
As a significant export commodity, palm oil and its derivatives, CPO, are essential for Indonesia. It opened considerable oil palm plantations in Indonesia, so in the end, Indonesia became the largest palm oil producer in the world. This research determines the impact of the oil palm plantations on achieving the Sustainability Development Goal of the community around the oil palm plantations of PT. DDP Ipuh District, Mukomuko Regency. Observation methods and interviews with 20 people were used to conduct the qualitative research. This study found that communities close to oil palm plantations earn better incomes after farming oil palm and educating their children to a higher level. The community employed local workers as plantation employees. In addition, the enthusiasm of the surrounding community to worship has increased. The impact of oil palm plantations has provided a change in circumstances for the community and a change in the community's mindset. People with limited living costs, limited children's education, and limited health change for the better. This way, the sustainable development goals (SDGs), especially the goals of no poverty, zero hunger, good health and wellbeing, and better quality education, can be accomplished